Whole-genome phylogenetic analysis of Mycobacterium avium complex from clinical respiratory samples - Chew Ka Lip; Joelle Go; Nur Aisyah Binte Abu Bakar; Sophie Octavia; Raymond Tzer Pin Lin; Jeanette W. P. Teo (Microbiology Spectrum)
ABSTRACT The Mycobacterium avium complex (MAC) is a common causative agent causing nontuberculous mycobacterial (NTM) pulmonary disease worldwide. Whole-genome sequencing was performed on a total of 203 retrospective MAC isolates from respiratory specimens. Phylogenomic analysis identified eight subspecies and species. M. avium subspecies hominissuis (MAH) was the overwhelmingly dominant species (148/203, 72.9%). The other seven identified species were M. intracellulare subsp. yongonense (18/203, 8.9%), M. intracellulare subsp. chimaera (10/203, 4.9%), M. colombiense (11/203, 5.4%), M. paraintracellulare (6/203, 3%), M. marseillense (5/203, 2.5%), M. intracellulare (3/203, 1.5%), and M. avium subspecies paratuberculosis (2/203, 1%). Significant genetic clustering was observed among MAH isolates. Notably, a large cluster (<12 SNPs) of 76 MAH isolates bearing the same sequence type was observed. The presence of closely related isolates within hospital settings raises concerns about transmission routes with environmental sources potentially playing a significant role. Based on susceptibility breakpoints that are available for clarithromycin, amikacin, linezolid, and moxifloxacin, low rates of clarithromycin (0.5%, 1/203) and amikacin (1.5%, 3/203) phenotypic resistance were observed. While linezolid and moxifloxacin resistance were 25.6% (52/2030) and 46.3% (94/203), respectively. Drug resistance-associated loci were searched for mutations linked to phenotypic drug resistance. Of the entire cohort, only one isolate was found to have a A2059G 23S rRNA (rrl) gene mutation responsible for macrolide resistance.IMPORTANCEMycobacterium avium complex (MAC) infections are increasingly challenging to manage due to their complex species diversity and varied resistance patterns. This study underscores the genetic diversity within MAC, identifying at least eight species and subspecies among 203 clinical isolates, with M. avium subsp. hominissuis (MAH) being most prevalent at 72.9%. Notably, genetic clustering was observed within MAH and M. intracellulare subsp. chimaera, suggesting potential transmission routes within healthcare settings. Clarithromycin and amikacin resistance was found to be uncommon, aligning with the rarity of resistance-associated genetic mutations. These findings emphasize the need for enhanced infection control measures and routine susceptibility testing to tailor antibiotic therapies effectively.